2009
DOI: 10.1017/s1368980009991522
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of breast-feeding initiation and duration in a sample of women in Ireland

Abstract: Objective: To assess breast-feeding initiation and prevalence from birth to 6 months in a sample of mothers in Dublin, and to determine the factors associated with breast-feeding initiation and 'any' breast-feeding at 6 weeks in a sample of Irish-national mothers. Design: This prospective cross-sectional study involved the recruitment of women during the antenatal period, with subsequent follow-up of mothers who delivered healthy, term singleton infants, at 6 weeks and 6 months postpartum. Setting: Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
90
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 66 publications
(80 reference statements)
5
90
1
3
Order By: Relevance
“…These data from the Cork BASELINE Birth Cohort Study are the most detailed and largest prospectively collected We have shown that although the rate of breast-feeding initiation has increased (9) , breast-feeding duration has not increased in Ireland. These trends are also reflected in the UK (11,12) .…”
Section: Discussionmentioning
confidence: 99%
“…These data from the Cork BASELINE Birth Cohort Study are the most detailed and largest prospectively collected We have shown that although the rate of breast-feeding initiation has increased (9) , breast-feeding duration has not increased in Ireland. These trends are also reflected in the UK (11,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Infants who were not breastfeeding may expose to higher risks of infectious morbidity, as well as associated with increased risks of childhood obesity, leukemia, type I and II diabetes and sudden infant death syndrome (SIDs) (Stuebe, 2009). Breastfeeding intention is a significant predictor of positive breastfeeding outcomes, having an intention to breastfeed linked to early initiation and longer duration of breastfeeding (Donath & Amir, 2003;Mitra, Khoury, Hinton, & Carothers, 2004;Tarrant, Younger, Sheridan-Pereira, White, & Kearney, 2010a). Intention is an immediate precursor of behaviour and is defined as the perception of an individual towards performance of a particular behaviour (Ajzen & Fishbein, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In this study breastfeeding intention was defined as the degree of confidence about practising optimal breastfeeding behaviour. Intention to breastfeed is closely related to early initiation to breastfeed and could also be a predictor of longer duration of breastfeeding (Tarrant, Younger, Sheridan-Pereira, White, & Kearney, 2010b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midwives provide antenatal, labour and postnatal care. Once a woman is discharged from hospital, postnatal care is provided by the GP and public health nursing service.Research has shown that women face different issues when breast-feeding such as not being adequately prepared for breast-feeding (4,5) , feeling embarrassed about breast-feeding in public (6)(7)(8) , perceiving insufficient milk supply (9,10) and receiving conflicting advice that subsequently undermines their confidence (11,12) . In addition, breast-feeding has been described as a 'problematic social act' whereby women try and find a balance between the act of breast-feeding and the needs, expectations and comfort of others (13) .…”
mentioning
confidence: 99%